Unemployment Duration and Earnings of Re-Employed Workers in Urban China. - Knight, J; Li, S (2006)
The recent draconian program of labor retrenchment in China caused widespread unemployment. Many of the retrenched workers remained unemployed for a long time. How did the duration of their unemployment affect their re-employment earnings? The possible relationships between unemployment duration and subsequent wages are modelled heuristically, four explanations for a negative relationship being found. This hypothesis is investigated by means of a survey of workers in 13 Chinese cities, conducted in 2000. Re-employment earnings are found to decline as unemployment continues, an effect that is both statistically significant and quantitatively important. China's displaced workers face a tough labor market.